Comprehensive assessment of coastal tourism potential in Vietnam - Hoang Thi Thu , Huong; Dang Kinh , Bac; Van Rompaey, Anton (Vietnam Journal of Earth Sciences, 2022)
Coastal tourism includes diverse resources and activities, so a comprehensive assessment is required to implement the sensible use of tourism potential. This paper deals with a comprehensive assessment of tourism potential in the coastal region of Vietnam based on 4 dimensions: attractiveness, accessibility, tourism service quality, and environmental quality & safety, covering 23 criteria. Analysis Hierarchy Process (AHP), Principal Component Analysis (PCA), Correlation analysis, and a Geographic Information System (GIS) were used in this study. AHP was applied to determine a weighting coefficient for each criterion. PCA was processed next to AHP, allowing a combination of the considered sites’ internal and external tourism potentials. Then the relationship between tourism potential and revenue is tested based on correlation analysis. The results show that the provinces in the South-Central region have the highest potential for coastal tourism development, followed by the North Central region. The Northern and Southeast region provinces and Mekong River Delta have low potential. However, there are still some bright spots for coastal tourism development in these regions, such as Quang Ninh, Ho Chi Minh City, Ba Ria-Vung Tau, and Kien Giang. This research also shows that tourism revenue depends more on external factors (supporting factors) than internal factors (tourism resources). Finally, the study proposed development plans for each group of coastal provinces based on their strengths and weaknesses, as well as suggested solutions to overcome the limitations of seasonality and the impact of climate change on Vietnam’s coastal tourism.